The effect of guided inquiry with differentiated learning to enhance students' critical thinking skills - Ningsih, Widia; Sipayung, Dwi Yanti Cornelia; Simatupang, Halim (Universitas Islam Negeri Sumatera Utara, 2025)
This study was designed to determine the effect of guided inquiry model integrated with differentiated learning on students' critical thinking skills on respiratory system material in class VII junior high school. The background of this research is based on the low critical thinking skills of students in Indonesia, as well as the need for a learning approach that is able to respond to the diversity of learning styles, interests, and readiness of students in the classroom. The guided inquiry with differentiated learning model, employs a method of instruction that encourages students to solve problems through the application of analytical and critical thinking skills. The present study employs a quasi-experimental design, specifically pretest-postest control group design. The present study utilizes a critical thinking ability test instrument according to Ennis, comprising 10 essay questions. Hypothesis testing was carried out with a significance level of 0.05 with the help of SPSS version 26. The research results demonstrated a significant influence of the guided inquiry learning mode with differentiated learning on students' critical thinking abilities, as measured by the Mann-Whitney U test with Asymp scores. Sig (2-tailed) 0.000, indicating a significance value <0.05. In conclusion, guided inquiry with differentiated learning is effective to enhance students' critical thinking skills and can be an alternative adaptive and responsive science learning strategy in the Merdeka Curriculum.